Advocacy and self‐advocacy in Malta: Reflections on the lives of Maltese people with intellectual disability from the 1950s to the present day. (6th February 2022) - Callus, Anne‐Marie; Bonello, Isabel; Micallef, Brian
Abstract: Background: This article presents an overview and discussion of the main developments in the lives of persons with intellectual disability in Malta over the last 70 years in residential services, education, employment, friendships and relationships, culture, sport and leisure activities, having a say in one's own life and how people look at persons with intellectual disability. It also discusses who were the people who played important parts in these developments. Materials and Methods: The article is written by an academic and two self‐advocates with lived experience of intellectual disability. The first author wrote the literature review tracing developments in the disability sector in Malta. These topics were then discussed by the three authors. Results: Thanks to these developments, persons with intellectual disability can live more independently in their community and develop their potential, including the ability to speak for themselves. However, many persons with intellectual disability do not have a say over how they live their lives and experience a lot of control. Very often, it is other people who decide for them. Persons with intellectual disability should enjoy relationships in which they are cared for and they care for others. They should also play an important part in the development of services that are aimed at them. Conclusions: The authors composed a poem which reflects the main issues that the two self‐advocates consider to be the most important: support, other people's attitudes and knowing what persons with intellectual disability want. Accessible summary: The lives of people with intellectual disability in Malta have improved a lot over the past 70 years. People used to be completely cut off from society and from their community and there were no support services at all until the 1960s. From the 1960s onwards, different services, welfare benefits and laws were put in place that have made it possible for people with intellectual disability in Malta to live better lives. Thanks to the support they have received, people have achieved a lot and have shown how capable they are. People with intellectual disability can speak themselves, make choices and take decisions but they do not always have the opportunity to do so. It is very important that others listen to what they have to say about their lives and base decisions on what these people say that they need and want.